Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Padi Sawah Tadah Hujan di Desa Lampanah Tunong Kecamatan Indrapuri Kabupaten Aceh Besar - Ikwanuddin Ikwanuddin; Syarifuddin Syarifuddin; M. Nasir Ismail; Zahrul Fuadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The purpose of this study was to determine the factors that influence the income of rainfed rice farming in Lampanah Tunong Village, Indrapuri District, Aceh Besar District. This research was conducted using the census method on 20 rainfed rice farmers. The analytical model used is Multiple Linear Regression. The results showed that land area had a significant effect on farm income, while the variables, urea fertilizer, SP36 fertilizer, NPK fertilizer, pesticides, production costs and labor did not significantly affect the income of rainfed lowland rice farming. The R2 value of 0.808 indicates that the close relationship between the independent variable and the variable is 80.8% while the remaining 1.20% is explained by other factors outside the model